(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article highlights the importance of translation studies on idiostylistics. The basic mechanisms of comparison are explored for revealing their inherent pragmatic sense relations. The functional and stylistic differences between the original and the translation are analyzed to disclose the reasons and consequences of using translational transformations that render, specify, level off, or modify the author’s style.